Autoria e autorrepresentação em comunidades quilombolas da baixada maranhense como formas de luta: um diálogo entre a antropologia e a literatura brasileira - Lourenço, Valéria Correia (2017)
The following text, the result of a research for dissertation purposes, aims to bring a reflection on the representation of collective identities and traditional knowledge in both anthropology and Brazilian literature. For this, we think of ethnography as a moment of enlargement of the literary and anthropological frontiers. In addition, we analyzed the ways in which traditional knowledge of “quilombola” communities were represented both in newspapers and in some texts of Brazilian literature. However, realizing that these social agents, members of research, previously objects of studies of literature and anthropology, today have claimed the authorship of their stories and their self-representation, we bring the narrative of some of them and some of them so that they are present. We thus perceive that this representation can also be understood as a form of struggle by breaking with the external and stigmatizing classifications to which these agents are subjected daily.